Complete genome sequence of Dehalogenimonas lykanthroporepellens type strain (BL-DC-9T) and comparison to "Dehalococcoides" strains. Issue 2 (March 2012) - Siddaramappa, Shivakumara; Challacombe, Jean; Delano, Susana; Green, Lance; Daligault, Hajnalka; Bruce, David; Detter, Chris; Tapia, Roxanne; Han, Shunsheng; Goodwin, Lynne; Han, James; Woyke, Tanja; et al.
Abstract Dehalogenimonas lykanthroporepellens is the type species of the genusDehalogenimonas, which belongs to a deeply branching lineage within the phylumChloroflexi . This strictly anaerobic, mesophilic, non spore-forming, Gram-negative staining bacterium was first isolated from chlorinated solvent contaminated groundwater at a Superfund site located near Baton Rouge, Louisiana, USA.D. lykanthroporepellens was of interest for genome sequencing for two reasons: (a) an unusual ability to couple growth with reductive dechlorination of environmentally important polychlorinated aliphatic alkanes and (b) a phylogenetic position that is distant from previously sequenced bacteria. The 1, 686, 510 bp circular chromosome of strain BL-DC-9T contains 1, 720 predicted protein coding genes, 47 tRNA genes, a single large subunit rRNA (23S-5S) locus, and a single, orphan, small subunit rRNA (16S) locus.